Diabetes Mellitus Counseling In Rt 06, Suka Maju Village, Mukomuko District - Nurkhasanah, Ria Devita; Anggraeni , Lora; Indhika , Vera; Febriani , Jummaria; Zuhairoh, Zuhairoh (Jurnal Inovasi Kerja Nyata, 2025)
The prevalence of diabetes increases in line with lifestyle changes such as lack of exercise and often consume unhealthy foods such as fast food (fast food), which occurs in many countries today. For now, diabetes can attack anyone, including children, adolescents, adults and parents. This socialization and education activity aims to help reduce the number of people with diabetes mellitus in RT 06 Village Suka Maju. Diabetes Mellitus is a disease that is always included in the ranking of 10 most diseases based on he number of visits at the Penarik Puskesmas Mukomuko Regency. The method used in socialization and education is the translation of diabetes mellitus such as risk factors, complications, discipline in taking drugs and dietary mellitus diet. In addition to the translation there is also an educational video that is played before the start of counseling to all the elderly present. Thus it is expected that public knowledge about diabetes mellitus will be even greater so that it will be able to reduce the rate of growth of people with diabetes mellitus.